2009
DOI: 10.1111/j.1467-9701.2009.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade, Tariffs and Total Factor Productivity: The Case of Spanish Firms

Abstract: The aim of this paper is to examine the sensitivity of total factor productivity (TFP) to foreign competition in the case of a European country. Using the Olley and Pakes (1996) method, we calculate the TFP of Spanish manufacturing firms and study the impact of EU tariffs, foreign competition and imports on TFP at the firm level. Applying the System-GMM method, we find that TFP is negatively impacted by European tariffs, whereas the competition, in the form of increased presence of foreign products in the dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…The results of the research revealed that trade reforms, licensing policy, reduction or elimination of trade barriers in the researched South African countries significantly increased their trade openness and productivity in the short run. Dovis & Milgram-Baleix (2009), who analysed the impact of competitiveness on productivity of Spanish manufacturing firms in the context of trade liberalisation, established a negative link between productivity and international trade tariffs. What is more, it was found that higher degree of competitiveness has a positive impact on productivity in case trade tariffs are eliminated.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…The results of the research revealed that trade reforms, licensing policy, reduction or elimination of trade barriers in the researched South African countries significantly increased their trade openness and productivity in the short run. Dovis & Milgram-Baleix (2009), who analysed the impact of competitiveness on productivity of Spanish manufacturing firms in the context of trade liberalisation, established a negative link between productivity and international trade tariffs. What is more, it was found that higher degree of competitiveness has a positive impact on productivity in case trade tariffs are eliminated.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…For a start, we follow [11][12][13] and use the "direct approach" to estimating production functions to estimate (1). To account for the simultaneity of input choices and unobserved productivity, we use the System-GMM estimator of Blundell and Bond (1998).…”
Section: Econometric Analysismentioning
confidence: 99%
“…The results of these regressions are reported in Tables 1 and 2. To assess the robustness of the findings, we apply a methodology that is similar to the one used by [1,[4][5][6]13] to study the correlation between total factor productivity 3 For example, if more productive firms are more likely to hire more workers and invest in more capital due to higher current and anticipated future profitability, estimation methods such as OLS will not be consistent and thereby result in biased coefficient estimates; the estimated input coefficients would be higher than their true values. 4 For example, in the specific case of the data set under examination, about 32 percent of observations has zero investment while a further 44 percent has "missing" investment and therefore much information would be lost in dropping these observations, as required by the Olley-Pakes technique.…”
Section: Econometric Analysismentioning
confidence: 99%
“…Findings on learning-by-importing is also inconclusive. Kasahara and Rodrigue (2008) for Chile, Smeets and Warzynski (2013) for Denmark, Halpern et al (2015) for Hungary, Forlani (2010) for Ireland, Dovis and Milgram-Baleix (2009) and Augier et al (2013) for Spain, and Lööf and Andersson (2010) for Sweden find evidence of productivity gain from importing. On the contrary, Muendler (2004) for Brazil, Vogel and Wagner (2010) for Germany, Van Biesebroeck (2008) for Colombia and Zimbabwe find weak evidence.…”
mentioning
confidence: 99%